(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
In order to produce and expand the range of export-oriented wine products from technical grape varieties, “cryoextraction” was studied as a non-traditional grape processing method for Uzbekistan. Scientific research has established the possibility of using cryoextraction of grapes grown in Uzbekistan to improve the physicochemical characteristics of wine materials. This method is promising in the technology of producing unique, high-quality wines that will harmoniously combine high acidity with high sugar content while maintaining the varietal aroma with an overlay of aroma formed by the production technology